THE EFFECT OF LIQUID ORGANIC FERTILIZER FROM CABBAGE WASTE ON THE GROWTH OF PAKCOY (Brassica rapa L. Var. Chinensis) - Syahmi Edi; Veby Emeninta Br Barus (Universitas Negeri Medan, 2023)
This study aims to determine the effect of liquid organic fertilizer from cabbage waste on the growth of mustard greens (Brassica rapa L. Var Chinensis). This research was conducted from March to May 2022 in Sukandebi Village, Naman Teran District, Karo Regency. This type of research is an experimental study with Non Factorial Completely Randomized Design, with 5 treatments and 5 replications. Analysis of research data used analysis of variance (ANOVA) with Duncan's multiple range test or Duncan's Multiple Range Test (DMRT). The parameters observed in this study were plant height, number of leaves, root length, fresh weight and dry weight. From the results of the study it was concluded that liquid organic fertilizer from cabbage waste had a significant effect on the observation of plant height, number of leaves, root length, fresh weight, and dry weight. The best growth of pakcoy mustard (Brassica rapa L. Var Chinensis), was at a dose of 500 ml/polybag. Meanwhile, the lowest growth of mustard greens (Brassica rapa L. Var Chinensis) was found in the control.